2013
DOI: 10.1182/blood-2012-12-475558
|View full text |Cite
|
Sign up to set email alerts
|

Trends in survival of patients with Burkitt lymphoma/leukemia in the USA: an analysis of 3691 cases

Abstract: Key Points Survival of patients with BL improved substantially in the United States during the past decade, mainly among young adults. Survival of patients with BL remains relatively low, particularly for older and black patients, identifying an unmet need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 20 publications
(26 reference statements)
6
59
1
1
Order By: Relevance
“…Our study did not find a statistically significant impact of advancing age on survival among patients treated with dose-intense chemotherapy regimens. This is similar to one recent study [Todeschini et al 2012], but contrasts with several other studies, including a systematic review [Kelly et al 2009] and two recent SEER registry studies [Castillo et al 2013;Costa et al 2013] which found poorer outcomes with advancing age. In the current study, only patients who received dose-intense chemotherapeutic regimens were included; thus, there was no age-associated difference in survival among patients deemed fit to receive dose-intense chemotherapy.…”
Section: Discussioncontrasting
confidence: 53%
“…Our study did not find a statistically significant impact of advancing age on survival among patients treated with dose-intense chemotherapy regimens. This is similar to one recent study [Todeschini et al 2012], but contrasts with several other studies, including a systematic review [Kelly et al 2009] and two recent SEER registry studies [Castillo et al 2013;Costa et al 2013] which found poorer outcomes with advancing age. In the current study, only patients who received dose-intense chemotherapeutic regimens were included; thus, there was no age-associated difference in survival among patients deemed fit to receive dose-intense chemotherapy.…”
Section: Discussioncontrasting
confidence: 53%
“…Considering that the majority of relapses occur during the first year after completion of treatment in BL we do not expect a relapse after almost 5 years remaining in complete remission. The results of the studies published by Costa et al [9] and Intermesoli et al [10] are in parallel with this opinion showing a high survival and a low relapse rate after 4 years in our patient's age group. However, there are no published cases of BL successfully treated with surgery alone.…”
Section: Dear Editorsupporting
confidence: 89%
“…However, it is unclear whether the source of the disparity is a lack of healthcare access, refusal of therapy or a distinct metabolism of chemoimmunotherapy in such demographic. Another population-based study using the SEER database that included pediatric patients also confirms our findings of poor outcomes in black patients with BL [10]. Furthermore, other epidemiological studies have associated blacks with worse outcomes in diffuse large B cell and Hodgkin lymphoma [11,12].…”
supporting
confidence: 72%